Bookkeeping and accounting [electronic resource] : based on Schaum's outline of theory and problems of bookkeeping and accounting, third edition, by Joel J. Lerner / abridgement editors, Daniel L. Fulks and Michael K. Staton. - Fulks, Daniel L.
Đầu trang nhan đề:Includes index.